Lactic acid bacteria from artisanal tanneries: isolation and evaluation of acidifyng ability - Correa Deza, Maria Alejandra (2015)
The tanning process allows to transform animal skin in stable and non-putrescible products namely leather. This process consists in various steps such as washing skins, liming, depilation, lime removal by washing, purging and tanning. During purging, the skins are immersed in a cereal mix which is let to ferment for 12-24 h at room temperature (18ºC-37°C). After this period, the pH decreased to 4.5-5.0, a condition that is required for the final steps. Under these homemade working conditions, the cereal fermentation is quite variable and affects the quality of the leather. The objective of this study was to isolate lactic acid bacteria (LAB) from the fermented cereal mixture in artisanal tanneries and to evaluate in vitro the acidifying activity of the strains. This is the first step for the formulation of a starter culture for tanneries to normalize the process.Samples of fermented cereals were taken from a tannery located in San Pedro de Colalao, Tucumán, Argentina, and colonies were isolated in MRS agar medium. The primary identification of the isolates included Gram stain, microscopic observations and catalase reaction. Gram positive, catalase negative strains (23) were cultured in a CERELA medium formulated for the production of lactic ferment and incubated at 18°C and 37°C for 24 h. At intervals, pH and titratable acidity (TTA) were determined. In most samples, a prevalence of cocci (95%) respect to bacilli was observed. The total isolated strains (56), 23 strains were Gram (+) and catalase (negative) which were selected. At 37 °C, most strains (21) acidified the culture medium within the first 8-h reaching a final pH ≤ 5.0 and a TTA ≥100ºD. At 18 °C, all strains showed a lower growth; however, the decrease in pH was 4.5-5.0 and the acidity developed (100-140ºD) after 24 hours of fermentation were similar to values obtained at 37°C. The best acid-producer strains were identified as Enterococcus faecium CRL 1943 and Leuconostoc citreum CRL 1945 by phenotypic and genotypic techniques. Currently, studies are being conducted to formulate a lactic inoculant on the basis of these strains and their metabolites for artisanal tanning.